Genetic differentiation of geographical populations of Liriomyza sativae (Diptera: Agromyzidae) in China based on mitochondrial COI gene sequences. (1st November 2016) - Du, Yu-Zhou; Tang, Xiao-Tian; Wang, Li-Ping; Shen, Yuan; Chang, Ya-Wen
Abstract: In this study, partial sequences of the mitochondrial cytochrome oxidase subunit I (COI) gene of four Liriomyza sativae (Blanchard) geographic populations in China were sequenced. As for the 784 bp mtDNA-COI gene obtained, six variable sites were found which were all transitions and no base composition was insertions or deletions. Six haplotypes were identified in all the sequences, with five showing polymorphism and one was exclusive. Nucleotide diversity (π) and haplotype diversity (h) ranged from 0.00068 to 0.00300 and 0.53571 to 0.82857, respectively. The phylogenetic trees suggested that six haplotypes constructed two clades. Molecular variance analysis (AMOVA) demonstrated that the genetic variation was not obvious and mainly occurred within geographic populations (94.8%). Most molecular variance within the species was due to the difference of haplotypes among different geographic populations. The genetic characters of the four populations were analyzed by FST value and gene flow ( Nm ), and the FST and Nm values were 0.174–0.464 and 0.577–2.367, respectively. All results showed that not only the gene flow presented among the four populations but also the genetic differences did. The main reason causing the genetic differences among the four populations was supposed to be related to geographic isolation and host plants aggravated the differences.